Generation of Neural Progenitor Cells From Canine Induced Pluripotent Stem Cells and Preliminary Safety Test in Dogs With Spontaneous Spinal Cord Injuries - Chow, Lyndah; McGrath, Stephanie; de Arruda Saldanha, Camila; Whalen, Lawrence R.; Packer, Rebecca; Dow, Steven (Frontiers in Veterinary Science, 2020)
Advances in stem cell technology, including the use of induced pluripotent stem cells (iPSC) to produce neurons and glial cells, offer new hope for patients with neurological disease and injuries. Pet dogs with spinal cord injuries provide an important spontaneous animal model for evaluating new approaches to stem cell therapy. Therefore, studies were conducted to identify optimal conditions for generating neural progenitor cells (NPC) from canine induced pluripotent stem cells (iPSC) for preliminary evaluation in animals with spinal cord injury. We found that canine NPC could be induced to differentiate into mature neural cells, including glia and neurons. In addition, canine NPC did not form teratomas when injected in NOD/SCID mice. In a pilot study, three dogs with chronic spinal cord injury underwent fluoroscopically guided intrathecal injections of canine NPC. In follow-up MRI evaluations, tumor formation was not observed at the injection sites. However, none of the animals experienced meaningful clinical or electrophysiological improvement following NPC injections. These studies provide evidence that canine iPSC can be used to generate NPC for evaluation in cellular therapy of chronic spinal cord injury in the dog spontaneous injury model. Further refinements in the cell implantation procedure are likely required to enhance stem cell treatment efficacy.